Acute hemorrhagic encephalitis in pediatric patient: a case report - Gavhane, Rushikesh; Jain, Abhishek; Pawar, Shilpa; Joshi, Trupti; Khaire, Prabha (International Journal of Contemporary Pediatrics, 2023)
Acute hemorrhagic encephalomyelitis (AHEM) is considered a rare presentation of acute disseminated encephalomyelitis (ADEM) and is challenging to manage. ADEM is a rare illness with an incidence of 0.2–0.4 per 100,000 children annually. Here we discuss a case report of a 3-year-old patient who presented with the clinical features of ADEM. On neuroimaging patient had a rare form of ADEM as hemorrhagic encephalitis. AHEM incidence is very low in the pediatric age group with poor prognosis. With the use of immunosuppressants and immunoglobulin, the survival of the patient was possible.